2017
DOI: 10.3390/met7120519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weld Current on the Microstructure and Mechanical Properties of a Resistance Spot-Welded TWIP Steel Sheet

Abstract: Abstract:In this study the effect of the weld current on the microstructure and mechanical properties of a resistance spot-welded twinning-induced plasticity (TWIP) steel sheet was investigated using optical microscopy, scanning electron microscopy-electron back-scattered diffraction (SEM-EBSD), microhardness measurements, a tensile shear test and fractography. Higher weld currents promoted the formation of a macro expulsion cavity in the fusion zone. Additionally, higher weld currents led to a higher indentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…Compared to the HAZ at the steel side, Figure 10 shows that the steel pseudo-NZs at all the welding parameters had more orientations with more HAGBs resulting in higher hardness [44,45]. This is in accordance with the results obtained by Tutar et al [46] who found that the NZ had higher hardness than the HAZ. Moreover, the HAZ had the lowest hardness compared to the BM and the pseudo-NZ, as proposed by Qiao et al [47].…”
Section: The Effect Of Microstructure and Texture On Mechanical Propesupporting
confidence: 87%
“…Compared to the HAZ at the steel side, Figure 10 shows that the steel pseudo-NZs at all the welding parameters had more orientations with more HAGBs resulting in higher hardness [44,45]. This is in accordance with the results obtained by Tutar et al [46] who found that the NZ had higher hardness than the HAZ. Moreover, the HAZ had the lowest hardness compared to the BM and the pseudo-NZ, as proposed by Qiao et al [47].…”
Section: The Effect Of Microstructure and Texture On Mechanical Propesupporting
confidence: 87%
“…In this paper, a novel refill technique is developed for friction stir spot welding (FSSW) using resistance spot welding (RSW), which is a popular manufacturing method in aerospace and automotive industries [16,17]. To demonstrate the validity of the technique, it is first applied to refill the keyhole created through FSSW of 1.5 mm thick AA2024 aluminum sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by adopting a rectangular terminal electrode, the electrode adhesion and splashing can be effectively reduced, and the connection strength of RSW joint can be increased. However, the welding current [11][12][13], pressure [14], time [15,16], and other parameters [17][18][19][20][21] in the RSW process have significant influence on the nugget dimensions and metallographic morphology of RSW joints. Compared with the traditional electrode, the distribution of welding current and welding pressure in the rectangular terminal electrode is much more complicated [22], which means that the welding parameters have more obvious influence on the nugget dimensions and metallographic morphology.…”
Section: Introductionmentioning
confidence: 99%